Predictors of hypertension among pregnant women - Andriani, Risca; Purba, Jenny Marlindawani; Bangun, Henny Arwina; Nababan, Donal; Tarigan, Frida Lina (Jurnal Prima Medika Sains, 2024)
This study investigated factors associated with hypertension during pregnancy (HDP) in Langkat Regency, Indonesia, where HDP cases have been increasing. Conducted at Sei Bamban Health Center between November 2023 and April 2024, the study included 47 third-trimester pregnant women. Data on maternal age, parity, BMI, family history of hypertension, secondhand smoke exposure, dietary habits, physical activity, and antenatal care (ANC) adherence were collected via questionnaires. Gestational hypertension was defined as systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg. Bivariate and multivariate analyses were performed using SPSS. While age and parity showed no significant association with HDP, elevated BMI (≥22.9 kg/m²) (p=0.010; OR 5.120; 95%CI: 1.427-18.373), a history of hypertension (p=0.016; OR 4.411; 95%CI: 1.282-15.174), exposure to cigarette smoke (p=0.000; OR 27.273; 95%CI: 3.165-235.024), low fat/salt intake (p=0.000; OR 0.088; 95%CI: 0.020-0.382), low physical activity (p=0.000; OR 31.667; 95%CI: 5.676-176.680), and non-adherence to ANC (p=0.000; OR 17.944; 95%CI: 3.391-94.948) were significantly associated with HDP. These findings highlight the importance of ANC adherence and risk factor management, including lifestyle modifications, for HDP prevention. The study recommends targeted education, counseling, screening, and monitoring of at-risk pregnant women.